2021
DOI: 10.5114/aoms/109170
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between KRAS, NRAS and BRAF mutations and tumor localizations in patients with primary and metastatic colorectal cancer

Abstract: IntroductionDetection of abnormalities in the KRAS, NRAS and BRAF genes is extremely important for proper qualification of colorectal cancer (CRC) patients for therapy with anti-EGFR monoclonal antibodies. However, data about prevalence of mutations in these genes, in different localizations of CRC tumors, is limited.Material and methodsWe examined the frequency of mutations in the KRAS, NRAS and BRAF genes in 500 Caucasian CRC patients (200 women and 300 men, median age – 66 years). DNA was isolated from form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
1
10
1
Order By: Relevance
“…A study on non-metastatic CRC patients found the mutation in 2/163 (1.22%) cases [16]. Two Polish studies on advanced CRC reported the incidence of BRAF V600E mutations in 24/500 (4.80%) and 7/102 (6.86%), respectively [17,18]. A recently published large study on the Russian population reported the incidence at 6.7% [19].…”
Section: Discussionmentioning
confidence: 99%
“…A study on non-metastatic CRC patients found the mutation in 2/163 (1.22%) cases [16]. Two Polish studies on advanced CRC reported the incidence of BRAF V600E mutations in 24/500 (4.80%) and 7/102 (6.86%), respectively [17,18]. A recently published large study on the Russian population reported the incidence at 6.7% [19].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that KRAS, NRAS and BRAF belong to the same signalling pathway, which makes the co-occurrence of their mutations extremely rare, as they are considered to be mutually exclusive. In fact, there is very little information on the biological behaviour of tumours with concurrent KRAS/BRAF mutations [8]. However, some studies have reported these concomitant mutations in KRAS and/or NRAS and BRAF presenting it as an indication of a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…To better understand CRC development, traditional research has focused on protein mutations, such as KRAS, NRAS and BRAF mutations 20 , and on DNA or RNA sequencing analysis. We believe that including DNA and RNA mutations, isoform appearance, and variant new versions will contribute to translating genotype into phenotype, and changes in status should be shown after related proteins are activated.…”
Section: Discussionmentioning
confidence: 99%